Legal Opinion: Nicaragua v. United States of America - Ilmi, Amadda (CV Rewang Rencang, 2020)
This case occurred between the United States and Nicaragua, where the problem between the two was a dispute that led to allegations of violation of international law, stemming from domestic governance problems that occurred in the Republic of Nicaragua. However, the United States is actively involved in these internal problems. Nicaragua considers that the interference by the United States has exacerbated the state of the Nicaraguan government and feels that the United States has acted in contravention of international law. One of the interventions was when America took steps to stop economic aid to Nicaragua because previously Nicaragua was against El Salvador, where El Salvador was known to have good diplomatic relations with America. Knowing this, America also carried out a kind of attack attempt by sending its military into the territory of Nicaragua and planting mines in the territorial sea and inland seas of Nicaragua, causing the ships passing by damaged or even destroyed. Then America also did its civil and military facilities in Nicaragua. Of course, this really bothered Nicaragua, because it did not make any efforts against America but was under attack for its case with El Salvador. The case was then reported to the ICJ who was the mediator and considered that the actions taken by America were wrong because they were too involved in matters that were not under its jurisdiction to participate in the case.